2015
DOI: 10.1007/s00268-015-3139-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Vagal Nerve Monitoring is Dangerous and Should not Routinely be Done During Thyroid Surgery

Abstract: We report the first evidence that CVNM may cause serious patient harm. This novel approach is invasive and threatens patient safety. Although it may occasionally provide meaningful information, the risk-benefit ratio does not favor widespread adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 25 publications
(27 reference statements)
1
55
1
3
Order By: Relevance
“…The measurements in this study were comparable to human standard values, supporting the porcine model as well‐suited for experimental neuromonitoring research . Hemodynamic instability caused by vagal stimulation, as described in humans, was not observed in this study. Body core temperature and blood pH values remained stable in both groups and within physiological limits throughout the experiments as a precondition for minimizing undesirable effects.…”
Section: Discussionsupporting
confidence: 83%
“…The measurements in this study were comparable to human standard values, supporting the porcine model as well‐suited for experimental neuromonitoring research . Hemodynamic instability caused by vagal stimulation, as described in humans, was not observed in this study. Body core temperature and blood pH values remained stable in both groups and within physiological limits throughout the experiments as a precondition for minimizing undesirable effects.…”
Section: Discussionsupporting
confidence: 83%
“…This methodological advantage makes LAR‐C‐IONM attractive for minimally invasive approaches, both endoscopic and open, in addition to alternative surgical approaches to neck endocrine surgery, such as transoral and transaxillary. Additionally, LAR‐C‐IONM is a safe technique that eliminates the need for manipulation of the vagus nerve and avoids the possibility of vagal electrode displacement intraoperatively, which disrupts the core analysis of the Automatic Periodic Stimulation system for detecting significant CMAP decrements …”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the only method of C-IONM requires placement of a stimulating electrode around the vagus nerve, which can become displaced intraoperatively and requires dissection between the common carotid artery and internal jugular vein. 10,11 In the first half of 2017, we published a case series of 15 patients whose RLNs were continuously monitored during thyroid and cervical spine surgeries using no equipment other than an EMG endotracheal tube. 12 Herein, we present the first large series of patients (100 patients, 134 nerves-at-risk) continuously monitored during neck endocrine procedures using the laryngeal adductor reflex (LAR-C-IONM), in addition to conventional I-IONM.…”
Section: Introductionmentioning
confidence: 99%
“…Now that the use of IONM during thyroid surgery and parathyroid surgery is increasing worldwide, the risk of bradycardia or hemodynamic stability followed by increased vagal tone is a growing concern. Terris et al reported an adverse cardiovascular event during continuous IONM in a healthy young female patient . According to the literature, most side effects of VN stimulation are apparently related to the use of a high‐frequency pulse or the use of continuous stimulation.…”
Section: Discussionmentioning
confidence: 99%